Caveolin‐1 up‐regulates integrin α2, 6‐sialylation to promote integrin α5β1‐dependent hepatocarcinoma cell adhesion. Issue 6 (14th February 2013) - Yu, Shengjin; Fan, Jianhui; Liu, Linhua; Zhang, Lijun; Wang, Shujing; Zhang, Jianing
Abstract : The alterations of integrin glycosylation play a crucial role in tumor metastasis. Our previous studies indicated that caveolin‐1 promoted the expression of the key α2, 6‐sialytransferase ST6Gal‐I and fibronectin‐mediated adhesion of mouse hepatocarcinoma cell. Herein, we investigated the role of α2, 6‐sialylated α5‐integrin in the adhesion of mouse hepatocarcinoma H22 cell. We demonstrated that caveolin‐1 up‐regulated cell surface α2, 6‐linked sialic acid via stimulating ST6Gal‐I transcription. Cell surface α2, 6‐sialylation was required for integrin α5β1‐dependent cell adhesion to fibronectin, and an increase in α2, 6‐linked sialic acid on α5‐subunit facilitated fibronectin‐mediated focal adhesion kinase phosphorylations, suggesting that α2, 6‐sialylated α5‐subunit promoted integrin α5β1‐dependent cell adhesion. Abstract : ► Caveolin‐1 regulates cell surface α2, 6‐sialylation via mediating ST6Gal‐I expression. ► α2, 6‐Sialylation participates in the binding of integrin α5β1 and fibronectin. ► α2, 6‐Sialylated α5‐subunit mediates integrin α5β1‐dependent cell adhesion. ► α2, 6‐Sialylated α5‐subunit is involved in modulating FAK signaling.